The principles and practice of bar and beverage management raising the bar - Murphy, James (Goodfellow Publishers Ltd, 2013)
A comprehensive text and resource book designed to explain the latest developments in and new complexities of managing modern bars- be they stand alone or part of larger institutions such as hotels and resorts.